Deposición de Carburo de Niobio por la Técnica de Deposición/Difusión Termorreactiva (TRD) en Aceros de Bajo Carbono (INGE@UAN - TENDENCIAS EN LA INGENIERÍA, 2011)
This research presents the deposition of niobium carbide on low carbon steels by the thermo-reactive deposition / diffusion technique using a SAE 8620 steel substrate. In order to obtain the needed carbide content for performing the deposition by the thermo-reactive deposition / diffusion technique, the substrate was case hardened with stay intervals of 2, 4, and 6 hours in the solid case hardening oven, using 60% charcoal and 40% barium carbonate, with barium as case hardening material, and subsequent annealing for structure homogenization. The chemical composition, case hardening depth and microhardness were characterized before and after case hardening. A new action field is opened for the TRD technique in low carbon steels whose application is developed in the metal-mechanical industry for example in manufacturing fixed wheels, differential sprockets and high revolution gears, among others, where the main goal is to increase the life cycle of these mechanical elements using the TRD carbide deposition technique.
Keywords: Niobium Carbide; thermo-reactive deposition/diffusion; case hardening; NbC; TRD